The Effects of Free Secondary School Track Choice: A Disaggregated Synthetic Control Approach - Aderonke Osikominu; Gregor Pfeifer; Kristina Strohmaier (Institute of Labor Economics (IZA), 2021)
We exploit a recent state-level reform in Germany that granted parents the right to decide on the highest secondary school track suitable for their child, changing the purpose of the primary teacher's recommendation from mandatory to informational. Applying a disaggre-gated synthetic control approach to administrative district-level data, we find that transition rates to the higher school tracks increased substantially, with stronger responses among children from richer districts. Simultaneously, grade repetition in the first grades of second-ary school increased dramatically, suggesting that parents choose school tracks also to align with their own aspirations – resulting in greater misallocation of students.
Keywords: C21; C46; I21; I28; J24; 330; school tracking; student performance; synthetic control method; treatment effect distributions; treatment effect heterogeneity